2020
DOI: 10.3390/life10100227
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptomic Analysis of NSC-34 Motor Neuron-Like Cells Reveals That Cannabigerol Influences Synaptic Pathways: A Comparative Study with Cannabidiol

Abstract: More than 120 cannabinoids were isolated from Cannabis sativa. In particular, Cannabidiol (CBD) and Cannabigerol (CBG) represent the two most studied non-psychoactive cannabinoids. However, CBG is less studied and less data are available on its biological properties and influence on synaptic transmission. On the contrary, CBD is already known to modulate brain excitatory glutamate, inhibitory γ-aminobutyric acid (GABA) and dopamine neurotransmission. In this study, using Next-Generation Sequencing (NGS) techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 62 publications
(64 reference statements)
2
14
0
1
Order By: Relevance
“…Our results might also add to previous pilot findings in healthy subjects suggesting some beneficial effects of THC-free hemp extracts on both autonomic nervous system regulation and brain function (Gugliandolo et al, 2020), although our participants exhibited no change in a measure of alpha activity (PAF). While more research is still required to more confidently determine the differential effects of hemp extracts on resting-state EEG rhythms, the present study might suggest a treatment resistant frequency-specific anomaly in the participant cohort we investigated.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our results might also add to previous pilot findings in healthy subjects suggesting some beneficial effects of THC-free hemp extracts on both autonomic nervous system regulation and brain function (Gugliandolo et al, 2020), although our participants exhibited no change in a measure of alpha activity (PAF). While more research is still required to more confidently determine the differential effects of hemp extracts on resting-state EEG rhythms, the present study might suggest a treatment resistant frequency-specific anomaly in the participant cohort we investigated.…”
Section: Discussionsupporting
confidence: 74%
“…Importantly, it has been reported that the administration of noradrenaline or dopamine agonists normalizes the theta/beta ratio (Clarke et al, 2003;Schutter & Van Honk, 2005). Given the evidence suggesting that both CBD and CBG might indirectly affect noradrenergic or dopaminergic transmission in the brain through the inhibition of CB1/CB2 receptors (Szabo & Schlicker, 2005) or selectively modulating gene expression (Gugliandolo et al, 2020), our results might suggest the ability of FOCUS to affect these mechanisms and future research should investigate the neurochemical substrates and pathways involved in region-specific slow versus fast wave EEG power regulation, in normal conditions and also in populations with a history of head injury.…”
Section: Discussionmentioning
confidence: 99%
“…CBD is known to potentiate GABA A -mediated inhibitory currents by acting on the GABA A receptor [65]. In accordance with this evidence, our research team in a previous work suggested that CBD might be able to decrease neuronal excitability in NSC-34 motor neuron-like cells through enhancing the expression of genes linked in GABA release and increasing the GABA A receptor gene expression [130].…”
Section: Gaba Receptorssupporting
confidence: 74%
“…Probably, as for the previous evidence, P13K/AKT pathway is responsible for the regrowth of dopaminergic neurons, while Parkin/PINK1 plays a role in neuroprotection [ 111 ]. We had also shown that CBD, along with cannabigerol (CBG) both at doses of 1 or 5 μM, is able to upregulate the expression of dopaminergic receptors 2 and 4 in NSC-34 cells, inhibiting at the same time the expression of monoamine transporter 2, decreasing in such way dopamine uptake [ 112 ], and this may also have a role in synaptic plasticity.…”
Section: Psychoactive and Non-psychoactive Cannabinoids Effects On Neurogenesismentioning
confidence: 99%